2008
DOI: 10.1007/s00239-008-9092-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversifying and Purifying Selection in the Peptide Binding Region of DRB in Mammals

Abstract: The class II genes of the major histocompatibility complex encode proteins which play a crucial role in antigen presentation. They are among the most polymorphic proteins known, and this polymorphism is thought to be the result of natural selection. To understand the selective pressure acting on the protein and to examine possible differences in the evolutionary dynamics among species, we apply maximum likelihood models of codon substitution to analyze the DRB genes of six mammalian species: human, chimpanzee,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 40 publications
7
44
0
Order By: Relevance
“…Thus, minor differences in the tree topology have little impact on our inference of positive selection under site models. Similar robustness of the site model analysis to the tree topology was also reported in other studies (Furlong and Yang 2008;Yang and Swanson 2002).…”
Section: Positive Selection Drives the Diversification Of Fprssupporting
confidence: 82%
“…Thus, minor differences in the tree topology have little impact on our inference of positive selection under site models. Similar robustness of the site model analysis to the tree topology was also reported in other studies (Furlong and Yang 2008;Yang and Swanson 2002).…”
Section: Positive Selection Drives the Diversification Of Fprssupporting
confidence: 82%
“…This was similar to the mammalian MHC class II DRB, even as Furlong and Yang (2008) found that almost all amino acid residues inferred to be under positive selection were in the PBD and in contact with the antigen side chains, although residues outside of but close to the PBD. In the evolution process, mutation of the amino acid sequence occurs in the non-PBD, destroying PBD structure integrity which makes MHC molecules fail in binding antigen peptides, while some mutations within the PBD increase the potential of MHC binding antigen peptides.…”
Section: Discussionsupporting
confidence: 68%
“…This kind of polymorphism is the result of natural selection (Furlong and Yang, 2008). In mammals, MHC gene region spans approximately 4 Mb, while in avian it is greatly reduced in size and gene content (Kaufman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these predicted sites were strongly and significantly correlated with the 15 peptide-binding region residues determined based on protein crystallography (Pearson's correlation ranged from r(29) ¼ 0.49, p , 0.01, primates, to r(12) ¼ 0.93, p , 0.001, rodents). In addition, these 15 sites are known to be involved with antigen binding and have been shown to be under positive selection across a diverse set of taxa (carnivores, rodents and primates [41]; bats [42]). Therefore, we focus analyses on these documented 15 ABS sites, though analyses with putative taxonspecific ABS sites show overall consistent results (see the electronic supplementary material, figure S3).…”
Section: Materials and Methods (A) Major Histocompatibility Complex Datamentioning
confidence: 99%